Empirical challenges comparing inequality across countries: The case of middle-income countries from the LIS database - Daniele Checchi; Andrej Cupak; Teresa Munzi; Janet C. Gornick (Luxembourg Income Study (LIS), 2018)
This study presents new empirical results, using microdata from the LIS database, on development patterns in economic inequality for a set of countries that are less covered in the empirical literature, mostly due to the lack of appropriate data. After discussing the main challenges when harmonizing income and consumption microdata from middle-income countries, we focus on Brazil, China, India, Russia, and South Africa, in a comparative perspective, and we compare them with a selection of benchmark middle- and high-income countries. We also run country-level regressions to correlate the inequality measures with selected macroeconomic indicators.
Keywords: D31; D63; O1; 330; economic development; equality; Luxembourg Income Study; middle-income countries; survey data